HERPES TYPE-2 VIRUS AND CARCINOMA OF THE CERVIX UTERI IN NIGERIANS: IMMUNOVIROLOGICAL STUDIES (1976)
In the search for the etiology of carcinoma of the cervix uteri, various factors have been implicated by various workers. The disease has been shown to have a venereal origin, following on its significant association with coital characteristics. These include early Initiation into hetero-sexual acts and frequency of coitus, multiplicity of coital Partners, multiparity, low socio-economic standards, venereal diseases and circumcision. Extensive epidemiologic studies have indicated that a "venoreally transmitted factor" might be responsible for the introduction of the squamous cell variety of the malignant disease. Recently, a strain of Herpes Simplex virus, antigenically distinct from the strain commonly associated with oral lesions, and designated Genital Herpes or Herpes Type-2 (HT-2) virus, was shown to be venereally transmitted, and might have oncogenic potentialities on the cervix. At the time the present studies were contemplated, little was documented about the clinical and histopathologic presentation of Carcinoma of the cervix in Ibadan. There was also no knowlege of the prevalence of Herpes Type-2 virus antibodies in the population, nor of the precise relationship, if any, of the virus to carcinoma of the cervix uteri in Ibadan. It was clear however, as a result of the work Edington and Maclean (1965) that carcinoma of the cervix uteri is very common in Ibadan, where it was shown to form the commonest female malignancy. Clinical, cytologic, histopathologic and immuno-virologic studies were undertaken to see if indeed carcinoma of the cervix uteri has a venereal origin, and to ascertain whether or not there is any association between the malignancy and HT-2 virus infection in Ibadan. In addition, sero-epidemiologic studies were also undertaken to determine the prevalence of HT-2 virus antibodies in various sectors of the Population. Evidence was provided to show that coital practice was a significant correlate of carcinoma of the cervix in Ibadan. Furthermore, Imuno- fluorescence and complement fixation tests were two Parameters used to provide evidence that Herpes Type-2 virus is associated with the disease, in that carcinoma of the cervix patients possessed significantly levels of antibodies against HT-2 virus as compared with patients having extra-cervical pelvic, and extra-pelvic malignancies and healthy Controls. In addition, HT-2 virus antigens were detected by immunofluorescence tests in the exfoliative cervical cells from all patients with carcinoma of the cervix, whereas no such virus antigens were found in exfoliated cervical cells from healthy Controls. In was concluded, that the observed association between HT-2 virus and carcinoma of the cervix in agreement with other studies, and the fact that the virus was not associated with other extra-cervical malignancies in this environment, indicate a significant relationship. Even though this may not necessarily be an etiologic one, the precise relationship of the virus and the malignancy would have to await further investigation.